Euripides, ion 444-451: - Obsieger, Hendrik (Prometheus (Italy), 2019)
Against a widespread interpretation, I argue that in vv. 444-447 Euripides is not alluding to an Attic lawsuit called δίκη βιαίων, and that in v. 448 προµηθία does not mean something like “foresight” or “care”, but rather is used synonymously with αδώς. Consequently, I reject the thesis that in Ion's monologue (vv. 429-251) almost all emphasis is on Apollo's supposed negligence of Kreusa and the begotten child, and none on the rape.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Apollo; Attic Law; Euripides; Ion; Rape

Plutarch: "De E apud Delphos", Über das Epsilon am Apolltempel in Delphi : Einführung, Ausgabe und Kommentar, - Obsieger, Hendrik (Franz Steiner Verlag, 2013)

Plutarch: De E apud Delphos - Über das Epsilon in Delphi. Einführung, Ausgabe und Kommentar - Obsieger, Hendrik (Franz Steiner Verlag, 2013)

Zu P. Erl. 1 = Nr. 2 Schubart - Obsieger, Hendrik (Zeitschrift für Papyrologie und Epigraphik, 2015)